2016
DOI: 10.1016/j.applthermaleng.2015.09.113
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental and application aspects of adsorption cooling and desalination

Abstract: Highlights Adsorption characteristics of various adsorbent-refrigerant pairs have been investigated. Adsorption cycle for sea water desalination has been introduced. Introduced the performance of hybridized adsorption and thermally driven cycle. Presented the costing of desalination methods by energetic and exergetic approaches. Page 1 of 19 Graphical AbstractPage 2 of 19 ABSTRACT Adsorption (AD) cycle is recently pioneered for cooling and desalination applications. For water treatment, the cycle can be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…After H sh is calculated for an effect, the height of the evaporating liquid film is determined as y = H -H sh , and is used in Eqs. (12), (14) and (16). It is noted that for all the cases studied in this work, the modeling results showed that the sensible heating height varied from 30 to 50 mm in the first effect to 10 to 20 mm in the last effect with an average height of about 20 mm.…”
Section: Sensible Heat Transfer To the Feed Watermentioning
confidence: 58%
See 1 more Smart Citation
“…After H sh is calculated for an effect, the height of the evaporating liquid film is determined as y = H -H sh , and is used in Eqs. (12), (14) and (16). It is noted that for all the cases studied in this work, the modeling results showed that the sensible heating height varied from 30 to 50 mm in the first effect to 10 to 20 mm in the last effect with an average height of about 20 mm.…”
Section: Sensible Heat Transfer To the Feed Watermentioning
confidence: 58%
“…They found that water production increase of 60%-78% could be achieved at the same heat source conditions due to the coupling. Saha et al [14] conducted experiments on a hybridized adsorption cycle with MED. Results demonstrated that the water production improved by 2-3-folds in a system consisting of a three-effect MED and adsorption plant with the top brine temperature at 50°C.…”
Section: Introductionmentioning
confidence: 99%
“…A schematic of the process is shown in Figure . Details of the AD cycle can also be found in the published literature . The AD cycle can be integrated with another thermally driven desalination system such as MED to improve the overall performance.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the AD cycle can also be found in the published literature. [24][25][26][27][28] TheA Dc ycle can be integrated with another thermally driven desalination system such as MED to improve the overall performance. Shahzad et al [29] conducted at heoretical study and simulated integration of an AD cycle with MED to extend the bottom brine temperature to as low as 10 8Cc ompared to ac onventional MED condenser, which has ab ottom brine temperature of 40 8C.…”
Section: Ad Cycle Operational Strategymentioning
confidence: 99%
“…Recent publications appearing in the literature [58][59][60][61][62][63][64][65][66][67][68][69][70][71] have made great strike towards improving the efficacy of practical desalination methods. In one example, the hybridization of the conventional MED method with the adsorption desalination (AD) cycles has been extensively investigated at the King Abdullah University of Science and Technology.…”
mentioning
confidence: 99%